Pengembangan Media Pembelajaran Neuroanatomi Berbasis WebXR (Website Extended Reality) dengan Pendekatan Aksesibilitas dan Optimalisasi - Gede Bramanda; I Gede Partha Sindu; Putu Hendra Suputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to develop and evaluate a WebXR (Website Extended Reality)-based learning media specifically designed for medical students at Universitas Pendidikan Ganesha. Neuroanatomy learning is a crucial yet challenging component of medical education, often difficult to comprehend due to limited learning media, the scarcity of cadavers, and the abstract nature of the SOBOTA anatomical atlas. The primary contribution of this research lies in the integration of an affordable and easily accessible web-based immersive platform, which simultaneously resolves technical constraints such as motion sickness and stuttering on standalone devices. Behind a well-structured and designed foundation, this media operates on a server-based infrastructure and runs on HTML5 technology architecture to deliver flexible, real-time data accessibility directly through the browser. Technical optimization was implemented in the form of FPS stabilization (FPS Locking) and dynamic resolution scaling to maximize the computing capacity of the Snapdragon XR2 chipset on Meta Quest 2. This application was built using the Multimedia Development Life Cycle (MDLC) framework. The assessment results show that the application has very high validity from both material and media experts, achieving an overall score of 1.00 based on the Gregory matrix. Furthermore, user experience testing using the User Experience Questionnaire (UEQ) with medical students yielded an